Chapter Notes on the writings by the University of the Witwatersrand students of Dante - Masciandaro, Franco (Studi e saggi, 2021)
I welcomed with enthusiasm the invitation to participate in the project of the young dantisti of the University of the Witwatersrand, as described by Chariklia Martalas: "To think critically about how the 21st century would change our views of Dante's Divine Comedy if we interpret it through creative form." I like to think of this project as a way, or method, that at once departs from and builds upon the traditional Dante studies. I therefore imagine that I am participating in a symposium, and therefore a dialogue with the young authors of this project, in the spirit of a newly discovered friendship.